Identification of brain‐targeted bioactive dietary quercetin‐3‐O‐glucuronide as a novel intervention for Alzheimer's disease. Issue 2 (24th October 2012) - Ho, Lap; Ferruzzi, Mario G.; Janle, Elsa M.; Wang, Jun; Gong, Bing; Chen, Tzu‐Ying; Lobo, Jessica; Cooper, Bruce; Wu, Qing Li; Talcott, Stephen T.; Percival, Susan S.; Simon, James E.; et al.
Abstract : Epidemiological and preclinical studies indicate that polyphenol intake from moderate consumption of red wines may lower the relative risk for developing Alzheimer's disease (AD) dementia. There is limited information regarding the specific biological activities and cellular and molecular mechanisms by which wine polyphenolic components might modulate AD. We assessed accumulations of polyphenols in the rat brain following oral dosage with a Cabernet Sauvignon red wine and tested brain‐targeted polyphenols for potential beneficial AD disease‐modifying activities. We identified accumulations of select polyphenolic metabolites in the brain. We demonstrated that, in comparison to vehicle‐control treatment, one of the brain‐targeted polyphenol metabolites, quercetin‐3‐ O ‐glucuronide, significantly reduced the generation of β‐amyloid (Aβ) peptides by primary neuron cultures generated from the Tg2576 AD mouse model. Another brain‐targeted metabolite, malvidin‐3‐ O ‐glucoside, had no detectable effect on Aβ generation. Moreover, in an in vitro analysis using the photo‐induced cross‐linking of unmodified proteins (PICUP) technique, we found that quercetin‐3‐ O ‐glucuronide is also capable of interfering with the initial protein‐protein interaction of Aβ1–40 and Aβ1–42 that is necessary for the formation of neurotoxic oligomeric Aβ species. Lastly, we found that quercetin‐3‐ O ‐glucuronide treatment, compared to vehicle‐control treatment, significantly improved AD‐type deficits in hippocampal formation basal synaptic transmission and long‐term potentiation, possibly through mechanisms involving the activation of the c‐Jun N‐terminal kinases and the mitogen‐activated protein kinase signaling pathways. Brain‐targeted quercetin‐3‐ O ‐glucuronide may simultaneously modulate multiple independent AD disease‐modifying mechanisms and, as such, may contribute to the benefits of dietary supplementation with red wines as an effective intervention for AD.—Ho, L., Ferruzzi, M. G., Janle, E. M., Wang, J., Gong, B., Chen, T.‐Y., Lobo, J., Cooper, B., Wu, Q. L., Talcott, S. T., Percival, S. S., Simon, J. E., Pasinetti, G. M. Identification of brain‐targeted bioactive dietary quercetin‐3‐ O ‐glucuronide as a novel intervention for Alzheimer's disease. FASEB J. 27, 769–781 (2013). www.fasebj.org